ANALISA POTENSI BUDIDAYA AIR TAWAR DAN PENGOLAHAN HASIL PERIKANAN KABUPATEN KONAWE UTARA, SULAWESI TENGGARA - La Ode Muhammad Arsal; Dedy Oetama; Haslianti; Ahmad Mustafa; Muhammad Trial Fiar Erawan; Chairun Annisa Aryanti (Techno-Fish, 2025)
Indonesia is the largest archipelago in the world with more than 81,000 km of coastline and more than 17,508 islands. The aquaculture and fishery product processing sectors have the potential to become one of the economic drivers in North Konawe Regency. There is a need for qualitative and quantitative information related to the development of the sector. The methodology used is; (1) survey and data collection, (2) data analysis using a set of analyses directed at mapping. (3) spatial database development. The land area of freshwater fish farming in North Konawe Regency is 11,928 ha, with potential land that can still be utilized amounting to 56,098 Ha. Commodities from freshwater aquaculture are dominated by goldfish, catfish and mujaer fish with a total production for 1 year of 5375 kg. Processing of fishery products in North Konawe Regency uses a traditional system and is on a household industry scale with a total of 88 business actors. The majority are located in Lasolo sub-district with a production of 145 tons/month. Tembang fish is the most dominating processing product at 90% of the total production. Based on the results of the study, we recommend the need to increase the area of freshwater aquaculture by opening new land to increase production. It is necessary to increase the capacity of business actors by modernizing the processing process and improving business institutions to be effective and efficient.